Severe Acute Respiratory Syndrome–Coronavirus-2 Infection and Patients With Lung Cancer: The Potential Role of Interleukin-17 Target Therapy - Cafarotti, Stefano (Journal of thoracic oncology, 2020)
The coronavirus disease 2019 outbreak is evolving rapidly worldwide. The lungs are the target of the primary infection and patients with lung cancer seem to have a poor prognosis. To our knowledge, this is the first reported investigation of a possible role of interleukin-17 target therapy in patients with lung cancer and concomitant severe acute respiratory syndrome–coronavirus-2 infection.